Muslim Women in South India: Reading Selected Narratives of Sara Aboobacker - Ayshath, S.R.; Raihanah., M.M.; Hashim, Ruzy Suliza (Asiatic: IIUM Journal of English Language and Literature, 2016)
This paper explores the narratives of Sara Aboobacker (1936-), a prolific South Indian Muslim woman writer. In her thirty years of literary production, Aboobackerâ€™s narratives showcase female characters from the South Indian Muslim community and highlight the varied experiences and the multiple identities they possess in a multicultural society. This study relies on the term â€œMuslimwomanâ€ coined by Miriam Cooke whereby she homogenises Muslim women all over the world. The study proposes that undifferentiating the female experiences of Muslim women as suggested by Cooke requires a more refined categorisation incorporating the heterogeneous identity of Muslim women especially in multicultural societies. The current reading attempts to address this concern with a two-part discussion of Aboobackerâ€™s narratives. The first part focuses on the three primary religious concepts of talaq or divorce, polygamy and purdah, and conveys that though Aboobackerâ€™s female characters are situated in a local environment, their concerns mirror some of the issues pertinent to Muslim women around the world. The second part problematises the gendered, inter-ethnic and inter-religious connections in Aboobackerâ€™s works through which she constructs the heterogeneous identity and experience of South Indian Muslim women parallel to the female issues of all downtrodden classes in a multicultural society like India. We contend that while Aboobackerâ€™s narratives provide us with an insight into the ways in which South Indian Muslim women navigate various pathways that demonstrate the magnitude of their challenges in integrating multiple identities, they should also be recognised for showcasing perennial, universal challenges relating to Muslim womenâ€™s rights globally.